Biologic activity of cyclic and caged phosphates: a review - Lorke, Dietrich E.; Stegmeier-Petroianu, Anka; Petroianu, Georg (Journal of applied toxicology, 2017)
The recognition in the early 1960s by Morifusa Eto that tri-o-cresyl phosphate (TOCP) is hydroxylated by the cytochrome P450 system to an intermediate that spontaneously cyclizes to a neurotoxic phosphate (saligenin phosphate ester) ignited the interest in this group of compounds. Only the ortho isomer can cyclize and clinically cause Organo Phosphate Induced Delayed Neurotoxicity (OPIDN); the meta and para isomers of tri-cresyl phosphate are not neuropathic because they are unable to form stable cyclic saligenin phosphate esters. This review identifies the diverse biological effects associated with various cyclic and caged phosphates and phosphonates and their possible use. Cyclic compounds that inhibit acetylcholine esterase (AChE), such as salithion, can be employed as pesticides. Others are neurotoxic, most probably because of inhibition of neuropathy target esterase (NTE). Cyclic phosphates that inhibit lipases, the cyclipostins, possibly represent promising therapeutic avenues for the treatment of type 2 diabetes mellitus and/or microbial infections; those compounds inhibiting β-lactamase may prevent bacterial resistance against β-lactam antibiotics. Naturally occurring cyclic phosphates, such as cyclic AMP, cyclic phosphatidic acid and the ryanodine receptor modulator cyclic adenosine diphosphate ribose, play an important physiological role in signal transduction. Moreover, some cyclic phosphates are GABA-antagonists, while others are an essential component of Molybdenum-containing enzymes. Some cyclic phosphates (cyclophosphamide, ifosfamide) are clinically used in tumor therapy, while the coupling of therapeutic agents with other cyclic phosphates (HepDirect® Technology) allows drugs to be targeted to specific organs. Possible clinical applications of these compounds are considered. Copyright © 2016 John Wiley & Sons, Ltd.